Shrine dedicated to Shiva at Hanuman Garhi temple complex - Temples of India Project Team (Jio Institute, 2024)
This is the biggest temple and one of the few living shrines of the Hanuman Garhi temple complex. Dedicated to Shiva, the temple consists of a garbhagriha (sanctum sanctorum) and a semi-open mandapa (pillared hall) connected via an antarala (vestibule or antechamber). The shikharas (superstructure) of both the garbhagriha and the mandapa are shekhari (multi-spired) shikhara and samavarna (bell roof) shikhara, respectively. The temple has undergone restoration, especially its superstructure.